PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN DAN UKURAN PERUSAHAAN TERHADAP RETURN ON ASSET PADA PERUSAHAAN DI JAKARTA ISLAMIC INDEX - Yanti, Indah Putri Febri; Usdeldi, Usdeldi; Muthmainnah, Muthmainnah (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
Profitability is the ability of a company to make a profit, indicated by profits generated from sales and investment income. High profitability will have a positive impact on the company because it can increase the value of the company, increase investor confidence, and can attract new investors to invest. Factors that affect high and low profitability include cash turnover, receivables turnover, inventory turnover and company size. This study aims to analyze the significant effect of Cash Turnover, Receivables Turnover, Inventory Turnover and Company Size on the return on assets of companies in the Jakarta Islamic Index 2018-2022. This study used a type of quantitative research. The data used is secondary data with the panel data regression analysis method with the help of the e-view 12 program to see a comprehensive picture of the independent variable against the dependent variable. The sample in this study consisted of 11 companies for 5 years obtained through www.idx.co.id website. The results of this study show that partially cash turnover, receivables turnover does not affect return on assets while inventory turnover and company size affect return on assets. The size of the company has a significant effect on return on assets. The results of the F test show that cash turnover, receivables turnover, inventory turnover and company size together have a significant effect on the return on assets of companies in the Jakarta Islamic Index 2018-2022.